2009
DOI: 10.1016/j.appet.2009.04.220
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric prefrontal cortex activation in relation to markers of overeating in obese humans

Abstract: Dietary restraint is heavily influenced by affect, which has been independently related to asymmetrical activation in the prefrontal cortex (prefrontal asymmetry) in electroencephalograph (EEG) studies. In normal weight individuals, dietary restraint has been related to prefrontal asymmetry; however, this relationship was not mediated by affect. This study was designed to test the hypotheses that, in an overweight and obese sample, dietary restraint as well as binge eating, disinhibition, hunger, and appetitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
7
26
2
Order By: Relevance
“…In a subsequent study conducted by the same research group , only right-sided parietal activity in the β2 (13-30 Hz) frequency range was a significant predictor of decreased AC. In any case, in both studies Morillas-Romero et al, 2013), results regarding the role of the parietal cortex fit with previous literature claiming that this brain area is critically involved in attentional capabilities (Kanai et al, 2011;Mevorach et al, 2009;Ochner et al, 2009;Posner and Rothbart, 2009) and processes (Deiber et al, 2007;McRae et al, 2010;Schutter et al, 2001;Szczepanski and Kastner, 2013) which, in turn, seem to be crucial to regulate emotions.…”
Section: Introductionsupporting
confidence: 89%
“…In a subsequent study conducted by the same research group , only right-sided parietal activity in the β2 (13-30 Hz) frequency range was a significant predictor of decreased AC. In any case, in both studies Morillas-Romero et al, 2013), results regarding the role of the parietal cortex fit with previous literature claiming that this brain area is critically involved in attentional capabilities (Kanai et al, 2011;Mevorach et al, 2009;Ochner et al, 2009;Posner and Rothbart, 2009) and processes (Deiber et al, 2007;McRae et al, 2010;Schutter et al, 2001;Szczepanski and Kastner, 2013) which, in turn, seem to be crucial to regulate emotions.…”
Section: Introductionsupporting
confidence: 89%
“…Our findings imply that connections of the anterior insula have larger leftward representation relative to the total insular gray matter volume; this leftward dominance of prefrontal and frontal connections coincides with the observations on forebrain asymmetry (Craig 2005) or lateralization of prefrontal activations, the latter already described as a biomarker for ingestive behaviour (Ochner et al 2009). Our result of a larger connectome of the left AI partially conflicts with the observation by Cauda et al (2011) where it was shown that the anterior cluster is rightward dominant; however, this type of interhemispheric dominance is marked by the strength (degree of temporal correlation) of functional and not structural connectivity.…”
Section: Laterality Of Connection Clusterssupporting
confidence: 73%
“…a dessert after dinner), but some experience more persistent preoccupation with palatable foods, defined as hedonic hunger (Finlayson, King, & Blundell, 2007;Lowe & Levine, 2005). The Power of Food Scale (PFS Lowe et al, 2009) measures this construct and is associated with frequency and intensity of food craving (Forman et al, 2007), as well as the development (Lowe et al, under review) and severity of binge eating in obese (Ochner, Green, van Steenburgh, Kounios, & Lowe, 2009) and eating disordered populations (Witt & Lowe, 2014).…”
Section: Introductionmentioning
confidence: 98%